GAMBARAN PENYAKIT PERIODONTALPADA WANITA MENOPAUSE DAN TIDAK MENOPAUSE DI PUSKESMAS SRONDOL, KOTA SEMARANG - Selvy Soejono; Henry Setyawan Susanto; Ari Udiyono; Mateus Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Periodontal disease is caused by the accumulation of bacteria that can cause inflammation in the surroundings tissues of supporting teeth, including gingivae, periodontal ligament and alveolar bone. Periodontal seems to be related with decrease estrogen levels in menopausal women, which can stimulate osteoclasts to resorb more bone because cytokines continues to produce immune cells (monocytes and macrophages) due to the challenges of plaque bacteria. This research was observational analytic with cross sectional study design. The population in this study are woman aged 30-65 totaling 100 respondents. The technique of sampling used consecutive sampling. Measurement of Periodontal disease using Community Periodontal Index for Treatment Needs (CPITN). Out of the 100 respondents, this study found 59,2% menopausal women with Periodontal disease. Advice given to menopausal women is to be able routine scaling in dentist every six months.